Teaching international students at a Russian technical university: psychological and pedagogical peculiarities; Technology, Education and Development Conference (INTED2017) - Sheveleva S. I. Svetlana Igorevna; Ponomareva L. A. Lyudmila Anatoljevna; Francuzskaya E. O. Evgeniya Olegovna; Starodubtsev V. A. Viacheslav Alekseevich (2017, 2017)
Title screen